Participatory disease surveillance, panacea to the bane of animal disease under-reporting in Nigeria: a collaborative report (2011)
Under-reporting of animal disease outbreak is a common feature in most developing countries with poor disease reporting system including Nigeria, where majority of animals are held by rural livestock farmers. Participatory Animal Disease Surveillance (PDS) a participatory epidemiology/epizootiology method which involves local rural livestock farmers, was developed in Africa as an accurate and rapid method to understand the distribution und dynamics of Rinderpest and has been recognized as a panacea to the existing bane of animal disease underreporting in third world countries by improving disease reporting, monitoring and surveillance in many developing countries This paper is a collaborative report of three Nigerian veterinarians in the academic, research und government services respectively towards finding a panacea to the bane of poor disease reporting and its attendant consequences A study was conducted in 2007 to evaluate the effectiveness of the operational system of the animal disease reporting system in Oyo State. Nigeria, one of the 36 States in Nigeria, for the period J995 to 2005 Generally the operations of the system in Oyo State are found to be ineffective in many aspects and characterized by late reporting, under-reporting and inaccurate data Between 2008 and 2009. PDS was applied in Nigeria under the Early Detection. Reporting and Surveillance for Avian Influenza in Africa (EDRSAJA) Programme and found to be logistically inexpensive, flexible, leads to timely control of diseases and can easily be integrated into the existing National Animal Diseases Information and Surveillance programme At the Department of Veterinary Public Health and Preventive Medicine. University of Ibadan. Nigeria. PDS have been incorporated into the postgraduate curricula since 2004 Other Veterinary Faculties in Nigeria are challenged to also incorporate PE/PDS in their curricula as part of needed training efforts relevant to addressing the bane of existing poor disease reporting and surveillance in Nigeria